Changing the pill: developments toward the promise of an ultra-long-acting gastroretentive dosage form. (2nd December 2018) - Altreuter, David H.; Kirtane, Ameya R.; Grant, Tyler; Kruger, Cecilia; Traverso, Giovanni; Bellinger, Andrew M.
ABSTRACT: Introduction : The development of oral sustained release dosage forms has been a longstanding goal due to the potential for ease of administration, improved pharmacokinetics, reduced dosing frequency, and improved adherence. The benefits of multiday single-dose drug delivery are evident in the success and patient adoption of injected and implanted dosage forms. However, in the space of oral medications, all current commercially available gastric resident dosage forms, and most in development, are limited to gastric residence of less than 1 day. Areas covered : Reviews of systems to extend gastric residence reveal that 1 day or more residence has been an unmet challenge. New dosage forms are in development that seek to address many of the key physiological and design challenges of long-term gastric retention beyond 24 h  and up to a week or longer. The present analysis highlights the design, material considerations and implications of unfolding dosage form systems with ultra-long-term gastric residence. Expert opinion : The development of oral dosage forms providing sustained release of high potency medications over days or weeks could transform care, significantly decrease patient burden in chronic disease management and improve outcomes.